2023
DOI: 10.1590/0102-672020230002e1723
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Sarcopenia Predicts Anastomotic Leaks and Long-Term Survival in Gastric Cancer Patients Operated With Curative Intent

Abstract: BACKGROUND: The preoperative nutritional state has prognostic postoperative value. Tomographic density and area of psoas muscle are validated tools for assessing nutritional status. There are few reports assessing the utility of staging tomography in gastric cancer patients in this field. AIMS: This study aimed to determine the influence of sarcopenia, measured by a preoperative staging computed tomography scan, on postoperative morbimortality and long-term survival in patients operated on for gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Our finding regarding the longer survival for resected patients is in agreement with other reports 6,15,24,32,33 . However, some other studies have shown different results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding regarding the longer survival for resected patients is in agreement with other reports 6,15,24,32,33 . However, some other studies have shown different results.…”
Section: Discussionsupporting
confidence: 93%
“…The description of the initial clinical characteristics of the patients in the present study corroborates this statement. However, progress in surgical technique and perioperative care has diminished this rate to less than 5% in recent studies 6 , 13 , 14 , 26 . In our study, palliative gastrectomy had a 30-day mortality rate of 5.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia and HRQoL are established risk factors for poor survival and tumor growth in upper GI tumors [ 10 , 12 , 19 , 41 , 62 , 63 , 64 , 65 , 66 , 67 ]. Sarcopenia has traditionally been measured through the CT-graphically obtained SMI, while HRQoL is obtained through patient questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect recently gaining importance as a clinical prognostic factor in upper GI cancers is sarcopenia, which has not only been shown to be prognostic for progress-free and overall survival [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], but also reportedly correlates with postoperative complications like pneumonia, and might even influence anastomotic leakage [ 31 , 35 , 39 , 40 , 41 , 42 ]. Specifically, loss of skeletal muscle during neoadjuvant treatment has been suggested to raise anastomotic leakage rates, while chemotherapy, according to the FLOT protocol, has been shown to raise sarcopenia rates from 16% to 33% [ 40 , 43 ].…”
Section: Introductionmentioning
confidence: 99%